Тренди, інструменти та перспективи сучасних технологій відеозйомки та монтажу - Кулик, О. О. (ХНУРЕ, 2025)
This paper examines the modern advancements in video shooting and editing technologies, emphasizing the transition from traditional filming techniques to AI-assisted and mobile-optimized approaches. It explores key trends in high-resolution cinematography, video stabilization, and the impact of artificial intelligence on automation and editing processes.
Keywords: відеозйомка; монтаж